Letramentos multimodais em um círculo de leitura: construção e (re)significação de sentidos na formação do leitor - Tavares, Mayara Corrêa (2024)
Reading is understood as multimodal and requires the reader to pay close attention to the construction of the text and its composition, even in literary works, which still privilege verbal elements. From this, this work thematizes the construction of meanings in a reading circle; its delimitation consists of the construction and meaning of meanings through (multi)literacies in a reading circle and the way in which this construction of meanings is elaborated by readers at the three levels of secondary education (1st, 2nd and 3rd years, in shifts morning and evening classes) at the Maria Dolores Freitas Barros State High School, located in the city of Passo Fundo/RS. The general objective is to analyze how students construct meanings and (re)signify them in the reading circle, based on their reading experiences. For this, assumptions were mobilized from the BNCC (Brazil, 2018), the Reference Curricular Gaúcho (Rio Grande do Sul, 2021), with regard to the documents that guide basic education in the country and in the state of Rio Grande do Sul, respectively. ; R. Yopp and H. Yopp (2001), Daniels (2002), Cosson (2020b, 2021) and Ousley-Exum [2022], in relation to the activities proposed in the reading circle; Larrosa (2019) and Petit (2009, 2013), regarding experience and literary reading; in addition to Kress (2010) and Kalantzis, Cope and Pinheiro (2020), regarding multimodality and multimodal literacies. Regarding the methodology, this research is exploratory with a qualitative approach and, according to the technical procedures, it is, at first, bibliographical and, afterwards, an action research was carried out through a focus group. The research corpus consists of: 1) the questionnaire, applied to students participating in the reading circle to identify literary interests; 2) the literary books selected and discussed in the reading circle; 3) selected materials (slide presentation, complementary readings) to complement the reading experience and those produced by students after reading, such as posters, reading diary - student production, presentation of authors and works It is organized by the researcher of this work; 4) the research diary organized by the author of this thesis. The thesis defended is that school-aged readers move between multimodal texts and that, from this, the construction of meaning in reading is updated as reading experiences are diversified and expanded, they are (re)signified, contributing to the training of (multi)literate subjects. The results obtained show that reading at school with a multimodal approach, whether through the reading circle or during Language classes, helps students to question the society they live in, making them critically aware, as well as more capable readers. Fruitful in relation to the different meanings, their constructions and the intention with which they are mobilized.